A Study on Prevalence of Pterygium at Sree Mookambika Institute of Medical Sciences - Dr. Divya Aleena Jacob, Dr. N. Rajendran, Dr. Kishore K Jacob, Dr. P.S. Indrapal; V Solanke, Dr. Prashant (International Journal of Innovative Research in Medical Science, 2017)
Background: Pterygium is a triangular fold of conjunctiva over cornea. Pterygium is more common in elderly male doing outdoor work. Risk factors are increasing age, male gender, outdoor occupation with ultraviolet (UV) light exposure, rural residence, cigarette smoking and drinking alcohol. Objective: Investigate the prevalence of pterygium and prevalence of its risk factors in a medical college hospital. Methodology: 67 patients were subjected to a cross sectional study by systematic random sampling with the participants of study being patients with pterygium coming to the ophthalmology OPD. Results: The prevalence of pterygium among the patients attending ophthalmology OPD is 9.2%. The sex based study shows that the prevalence of cataract is more among males. It is clear from the study that pterygium is more common among the persons doing outdoor work rather than indoor work.